2002
DOI: 10.2224/sbp.2002.30.8.821
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Reflection and Insight Scale: A New Measure of Private Self-Consciousness

Abstract: This paper was aimed at investigating the construction and validation of the SelfReflection and Insight Scale (SRIS) which is designed to be an advance on the Private SelfConsciousness Scale (PrSCS; Fenigstein, Scheier, & Buss, 1975). Previous work has found the PrSCS to comprise two factors, self-reflection and internal state awareness. In a series of studies two separate factor analyses found the SRIS comprised two separate factors labeled Self-Reflection (SRIS-SR) and Insight (SRIS-IN. The PrSCS correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
626
2
50

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 519 publications
(730 citation statements)
references
References 26 publications
(37 reference statements)
20
626
2
50
Order By: Relevance
“…The Self-Reflection and Insight Scale (SRIS) is a 20-item scale developed by Grant et al (2002). Compared to other similar scales for self-reflection or self-consciousness (e.g., Fenigstein et al, 1975;McKenzie & Hoyle, 1999;Trapnell & Campbell, 1999), one of the advantages of the SRIS is its delineation of the two different factors: self-reflection (SRIS-SR) and insight (SRIS-IN).…”
Section: Assessment Of Disposition In Self-reflectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Self-Reflection and Insight Scale (SRIS) is a 20-item scale developed by Grant et al (2002). Compared to other similar scales for self-reflection or self-consciousness (e.g., Fenigstein et al, 1975;McKenzie & Hoyle, 1999;Trapnell & Campbell, 1999), one of the advantages of the SRIS is its delineation of the two different factors: self-reflection (SRIS-SR) and insight (SRIS-IN).…”
Section: Assessment Of Disposition In Self-reflectionmentioning
confidence: 99%
“…This delineation of self-reflection versus insight converges with theoretical arguments on self-consciousness (e.g., Pinku & Tzelgov, 2006) and has found some support from empirical studies. For example, Grant et al (2002) found that SRIS-IN, but not SRIS-SR, was positively associated with cognitive flexibility. Lyke (2009) found that SRIS-IN, but not SRIS-SR, was positively associated with satisfaction with life and subjective happiness.…”
Section: Assessment Of Disposition In Self-reflectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many ways, this is not a surprising development; the pragmatic and effective nature of the approach matches the desire for efficient ways to make progress found in most organisations (Cavanagh & Grant, 2010;de Shazer, 1988;O'Connell, 1998). Although more and more solution-oriented people work in organisations, solution-focused approach is still widely seen as a therapy, coaching, training or facilitating approach, but not yet as a leadership style (Grant, Franklin, & Langford, 2002).…”
Section: Introduction mentioning
confidence: 98%